Song of the heart : selected poems - López Velarde, Ramón, 1888-1921 (Texas Pan American Series., 1995)
Ramón López Velarde (1888-1921) was one of the most Mexican of Mexican poets, whose sense of history found expression in many poems, including his best-known "La suave Patria" ("Sweet Land"). This bilingual collection, drawn primarily from Poesías completas y el minutero, offers English-language readers our first book-length introduction to his poetry. Often called a "poet of the provinces," López Velarde gives us a glimpse into a slower and more gentle way of life. His poems present the contrast between city and hometown and between urban and pastoral landscapes. Through these contrasts runs the thread of religious faith, while urgency of language informs the entire body of his poetic production. Original, specially commissioned drawings by noted contemporary Mexican artist Juan Soriano complement the poems. This combination of poetry and art speaks to universal emotions; indeed the poetry of López Velarde belongs to everyone who sings the Song of the Heart.